KEPEMIMPINAN KEPALA DESA DALAM PEMBANGUNAN FISIK DESA KOTA INTAN KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Hariana "; Harapan Tua (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
village chief, as leader of government within village scope should be able to perform their duties empirically, either as a public servant or as an intermediary who can provide solutions to the problems that arise in a society that covers the scope of the area under his authority. The aspirations submitted by society should be heard by a village chief so that their common goal can be achieved as expected. Also the physical development of the village must be considered by the village chief, because it will be needed by the villagers. But in fact, there are still some problems caused by the lack of village chief leadership on the physical development of Kota Intan village.The purpose of this study was to determine the village chief leadership on the physical development of Kota Intan Village Kunto Darussalam Subdistrict Rokan Hulu Regency, as well as factors that hinder the physical development of Kota Intan Village Kunto Darussalam Subdistrict Rokan Hulu Regency. To analyze the phenomenon in this study the author used Sondra P Siagian’s theory with indicators as follows : a leader as determinants directions, a leader as a representative and spokesperson, a leader as an effective communicator, a leader as a reliable mediator, and a leader as an effective integrator. Methodology used in this study is a qualitative descriptive study with Snowball sampling method.This study shows that Chief Village Leadership on Physical Development of Kota Intan Village Kunto Darussalam Subdistrict Rokan Hulu Regency is good. The factors found are funds, land disputes, lack of government attention and resources.Keywords: Village Chief, Leadership and Development.